Increased Intracranial Pressure on a Patient with Neuromyelitis Optica Spectrum Disorder - Seyed Mohammad Forouzannia; Pourya Yarahmadi; Mohammad Alirezaei; Nasim Rezaeimanesh; Abdorreza Naser Moghadasi (Babol University of Medical Sciences, 2021)
Background: Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune astrocytopathic disease affecting central nervous system (CNS). CSF pressure in these patients is usually normal. Case Presentation: A 30-year-old woman was admitted with complaints of headache and lower limbs paresis. Lumbar puncture (LP) and magnetic resonance imaging were performed for the patient. Opening pressure was 42 cm H2O in the first LP. According to the clinical evidences, imaging, and the patientchr('39')s positive aquaporin-4 antibody, the diagnosis of NMOSD was established. Conclusion: High intracranial pressure headache; however rare, may be the first sign of the onset of the acute exacerbation phase of NMOSD.